Fracture mechanisms of glass particles under dynamic compression. (August 2017) - Parab, Niranjan D.; Guo, Zherui; Hudspeth, Matthew C.; Claus, Benjamin J.; Fezzaa, Kamel; Sun, Tao; Chen, Weinong W.
Highlights: High speed synchrotron X-ray imaging was used to study the fracture of single and contacting glass particles. A modified Kolsky bar was used compress single, two, three, and five contacting particles dynamically. Cracking initiated under the particle-pin contact for single particle experiments. For multi-particle experiments, cracking initiated at the particle-particle contact and separated a fragment, which did not affect the ability of the particles to withstand loading. The final fracture mode for all experiments was explosive fragmentation. Abstract: In this study, dynamic fracture mechanisms of single and contacting spherical glass particles were observed using high speed synchrotron X-ray phase contrast imaging. A modified Kolsky bar setup was used to apply controlled dynamic compressive loading on the soda-lime glass particles. Four different configurations of particle arrangements with one, two, three, and five particles were studied. In single particle experiments, cracking initiated near the contact area between the particle and the platen, subsequently fragmenting the particle in many small sub-particles. In multi-particle experiments, a crack was observed to initiate from the point just outside the contact area between two particles. The initiated crack propagated at an angle to the horizontal loading direction, resulting in separation of a fragment. However, this fragment separation did not affect the ability of the particle to withstand further contact loading. On further compression, large number of cracks initiated in the particle with the highest number of particle-particle contacts near one of the particle-particle contacts. The initiated cracks roughly followed the lines joining the contact points. Subsequently, the initiated cracks along with the newly developed sub-cracks bifurcated rapidly as they propagated through the particle and fractured the particle explosively into many small fragments, leaving the other particles nearly intact. Graphical abstract: